Influence of Age on Cardiorespiratory Kinetics During Sinusoidal Walking in Humans - Ebine, Naoyuki; Ahad-Abdulkarim-D, Alharbi; Miyake, Yuki; Hojo, Tatsuya; Abe, Daijiro; Horiuchi, Masahiro; Fukuoka, Yoshiyuki (Frontiers in Physiology, 2018)
We sought to determine the influence of age on cardiorespiratory kinetics during sinusoidal walking in two groups: 13 healthy young subjects (YG; 7 men and 6 women, age 21±2 y) and 15 healthy elderly subjects (ELD; 9 men and 6 women, age 67±5 y). A treadmill's speed was sinusoidally changed between 3 km·h−1 and 6 km·h−1 in the YG and between 3 km·h−1 and 5 km·h−1 in the ELD during periods of 1, 2, 5, and 10 min, and in a stepwise manner. We compared the groups' heart rate (HR), ventilation (VE), and gas exchange (CO2 output (VCO2) and O2 uptake (VO2)) responses. We determined the phase shift (PS) and the normalized amplitude (Amp) ratio of these kinetics in relation to the sinusoidal change in walking speed in response to the magnitude from the maximum to minimum speeds as revealed by a Fourier analysis in all cardiorespiratory variables. Both the Amp ratio and PS in the VE, VCO2, and VO2 responses were very similar between the ELD and YG, and being independent of the periods of sinusoidal oscillations. In marked contrast, the PS of the HR kinetics was significantly slowed in the ELD compared to the YG. The Amp ratio of HR was not related to the covariance variation of HR (CVHR) at standing rest in the ELD. The HR kinetics during sinusoidal walking may not be attributable to parasympathetic nerve activity into the heart in the ELD. The slope of the Amp of VE related to the Amp of VCO2 (VE/VCO2 slope) was steeper in the ELD (0.0258) compared to the YG (0.0132), suggesting that exercise hyperpnea could be greatly induced during walking in the ELD. These findings suggest that aging influences the alterations of autonomic nervous system-dependent slower HR kinetics and exercise hyperpnea during walking in the ELD.